2020
DOI: 10.1111/pace.14106
|View full text |Cite
|
Sign up to set email alerts
|

Ablation catheter orientation: In vitro effects on lesion size and in vivo analysis during PVI for atrial fibrillation

Abstract: Background Catheter‐delivered radiofrequency (RF) lesion formation is a complex phenomenon, and few studies have explored the effect of catheter orientation on lesion size and catheter orientation behavior during pulmonary vein isolation (PVI) procedures. We evaluated the influence of catheter orientation on lesion dimensions in an in vitro experimental setting and investigated the catheter orientation behavior during PVI. Methods and results 72 lesions were created in vitro on a porcine heart using a contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…Recent in vitro study demonstrated by V. Calzolari et al [11] is consistent with our study. RF lesions created on a porcine heart with different contact angles were evaluated, and they measured both superficial lesion size and crosssectional lesion size.…”
Section: Rf Lesion Created In Different Catheter Contact Anglessupporting
confidence: 94%
See 1 more Smart Citation
“…Recent in vitro study demonstrated by V. Calzolari et al [11] is consistent with our study. RF lesions created on a porcine heart with different contact angles were evaluated, and they measured both superficial lesion size and crosssectional lesion size.…”
Section: Rf Lesion Created In Different Catheter Contact Anglessupporting
confidence: 94%
“…An in vitro study was conducted under limited setting of CF, ablation time, and power. To avoid steam pop phenomenon, lower CF and lower power were selected compared with other in vitro studies [11][12][13][14]. CF variability was not evaluated, and it is not clear whether the lesion size difference of in vitro study is clinically significant.…”
Section: Limitationsmentioning
confidence: 99%
“…Apart from the RF electrode insertion depth, we have also numerically investigated the effects of RF electrode orientation on the treatment outcomes of cardiac ablative procedures. Motivated by [55], three RF electrode to tissue orientations have been considered, viz., perpendicular (90 • ), oblique (45 • ) and parallel (0 • ), as depicted in Figure 6a. The temperature distributions obtained for these three orientations have been presented in Figure 6b-d considering ε = 0.3 and u in = 3 cm/s.…”
Section: Effect Of Of Electrode Orientationmentioning
confidence: 99%
“…Several studies have demonstrated that the catheter contact angle is an important factor in lesion creation. [16][17] [18] In an in vitro study, Calzolar et al reported [17] that the superficial lesion widths were increased by shifting the catheter angle from the perpendicular to the parallel orientation, and the intratissue maximal lesion widths were greater with an oblique catheter orientation than with a perpendicular position using a 3.5-mm tip, open-irrigated, CF-sensing catheter (TactiCath SE; Abbott, St. Paul, MN, USA). Conversely, they also reported that the lesion depths were not different with different catheter orientations.…”
Section: Correlation Between the Lesion Size And The Catheter Contact Anglesmentioning
confidence: 99%